2021
DOI: 10.1126/sciadv.abe2086
|View full text |Cite
|
Sign up to set email alerts
|

A circadian clock in a nonphotosynthetic prokaryote

Abstract: Circadian clocks create a 24-hour temporal structure, which allows organisms to occupy a niche formed by time rather than space. They are pervasive throughout nature, yet they remain unexpectedly unexplored and uncharacterized in nonphotosynthetic bacteria. Here, we identify in Bacillus subtilis circadian rhythms sharing the canonical properties of circadian clocks: free-running period, entrainment, and temperature compensation. We show that gene expression in B. subtilis can be synchronized in 24-hour light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 52 publications
2
73
0
1
Order By: Relevance
“…Oscillations involving excitation and decay can be identified across life. For example, excitable genetic switches are found in bacteria [ 52 ], belonging to circadian clocks in cyanobacteria [ 53 ], in other non-photosynthetic bacteria [ 54 ], in Drosophila [ 55 ] and in plants [ 56 , 57 ]. The molecular mechanisms identified in these systems point towards a malleable duration of the oscillations by mutations [ 52 , 58 ], modifications of the regulatory network [ 32 ] or degradation and destabilisation of protein complexes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oscillations involving excitation and decay can be identified across life. For example, excitable genetic switches are found in bacteria [ 52 ], belonging to circadian clocks in cyanobacteria [ 53 ], in other non-photosynthetic bacteria [ 54 ], in Drosophila [ 55 ] and in plants [ 56 , 57 ]. The molecular mechanisms identified in these systems point towards a malleable duration of the oscillations by mutations [ 52 , 58 ], modifications of the regulatory network [ 32 ] or degradation and destabilisation of protein complexes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although currently there is no evidence to support this idea, one can speculate that organelles might harbor their own internal clock. Of particular interest are mitochondria, in view of their evolutionary shared past with prokaryotes, some of which harbor a circadian clock [ 125 , 126 ]. However, unlike cells that can be cultured for days to weeks without any intervention, to date it has been virtually impossible to keep isolated organelles viable in culture for several days.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that while cyanobacteria have been considered to possess the archetypal bacterial clock, this notion has recently been challenged by the discovery of an oscillator in Bacillus subtilis carrying all the hallmarks of a circadian clock (Eelderink- Chen et al, 2021). The molecular mechanism for this clock remains to be elucidated, however, the lack of kai homologues in B. subtilis as well as the presence of Per-Arnt-Sim domains in its circadian genes, akin to eukaryotes, carries interesting implications for circadian clock origins.…”
Section: The Circadian Clock In Cyanobacteriamentioning
confidence: 99%
“…Given the recentness of the identification of a circadian clock in the non-photosynthetic bacterium B. subtilis (Eelderink- Chen et al, 2021), its robustness and potential coupling have yet to be explored. However, Eelderink-Chen et al noted when reporting their discovery that circadian rhythms were uniquely found in pellicle biofilm-forming cultures (Eelderink- Chen et al, 2021).…”
Section: Ll Open Accessmentioning
confidence: 99%